Pengaruh Manajemen Zakat Dan Transparansi Laporan Keuangan Terhadap Kepercayaan Muzakki Pada Baznas Kabupaten Bengkalis - Nurhafizah Nurhafizah; Siti Asiam (AKUNTANSI 45, 2021)
The purposes of this research are to determine the effect of zakat management and transparency of financial reports on muzakki's trust. This type of research is quantitative research with a descriptive approach. Questionnaires are used to collect data. The population in this study is all muzakki in BAZNAS Bengkalis Regency in 2019, totaling 1203 muzakki. In analyzing the data, researchers used multiple linear regression analysis. The result of the regression analysis is that the tcount value for the zakat management variable is 2.515> 1.98667 and the sig value is 0.014 <0.05, which means that zakat management has an effect on muzakki's trust. The tcount value of the variable transparency of financial reports is 5.208> 1.98667 and the sig value is 0.000 <0.05. So it can be concluded that the transparency variable of financial statements has an effect on muzakki's trust. Regression analysis shows that the Fcount value is 66,000> 3.10, which means that the zakat management variable and the transparency of financial statements have a simultaneous effect on muzakki's trust.